DIGITAL MOVEMENT OF OPINION MOBILIZATION FOR FOOTBALL TOURNAMENT FANS IN INDONESIA: SNA STUDY #PIALAMENPORA2021 VS #PERSIJADAY - Vina Devi Yekti Irawan; Osly Usman (Journal of Economics, Business, and Government Challenges, 2021)
This research examines the role of the #PialaMenpora2021 and #PersijaDay on Twitter in shaping the mobilization of digital opinion support, measuring network comparisons, actors between hashtags, and digital opinion. The theory used is the Digital Movement of Opinion by looking at the level of actors and systems. The method used in this research is to combine quantitative and qualitative methods. Quantitatively, this study looked at the communication network from a sample of 15,784 tweet data, with details of 7,456 #PialaMenpora2021 tweet data and 8,328 #PersijaDay tweet data using netlytic. Meanwhile, qualitatively, the researcher analyzed text that describes and explains social networks through library research. The results showed that both #PialaMenpora2021 and #PersijaDay are capable of creating mobilization. The success of the two of them has an extensive network and has a two-way interaction relationship in giving their opinions regarding the soccer tournament held in Indonesia